Analysis of Factors Affecting Income and Order Levels of Online Motorcycle Taxis During the Pandemic Case Study of Grab And Gojek Online Ojek Drivers In palopo City - Muh Ramli; Arianto Dangkeng; Hardianti Pertiwi; Rafika Fausiah (Universitas Muhammadiyah Makassar, 2023)
Analysis of Factors Affecting Income and Order Levels of Online Motorcycle Taxis During the Pandemic Case Study of Grab And Gojek Online Ojek Drivers In palopo City. This study was conducted to determine the income and number of orders as well as factors that affect the orders and income of online motorcycle taxi drivers during a pandemic. From the results of the study, it shows that the pandemic affects the income of online motorcycle taxi drivers, but there are also drivers who do not experience a decrease in income, a factor that affects the income of online motorcycle taxi drivers, namely the lack of orders because the number of online motorcycle taxi bookers everyday cannot be ascertained, online motorcycle taxi drivers who do not experience changes in income are drivers who are diligent and have many working hours